Longitudinal tracking reveals sustained polyclonal repopulation of human-HSPC in humanized mice despite vector integration bias - Gajendra W. Suryawanshi; Hubert Arokium; Sanggu Kim; Wannisa Khamaikawin; Samantha Lin; Saki Shimizu; Koollawat Chupradit; YooJin Lee; Yiming Xie; Xin Guan; Vasantika Suryawanshi; Angela P. Presson; et al. (My University, 2020)
Abstract Background Current understanding of hematopoiesis is largely derived from mouse models that are physiologically distant from humans. Humanized mice provide the most physiologically relevant small animal model to study human diseases, most notably preclinical gene-therapy studies. However, the clonal repopulation dynamics of human hematopoietic stem and progenitor cells (HSPC) in these animal models is only partially understood. Using a new clonal tracking methodology designed for small sample volumes, we aim to reveal the underlying clonal dynamics of human cell repopulation in a mouse environment. Methods Humanized BLT (bone marrow-liver-thymus) mice were generated by transplanting lentiviral vector transduced human fetal liver HSPC (FL-HSPC) in NOD.Cg- Prkdc scid Il2rg tm1Wjl /SzJ (NSG) mice implanted with a piece of human fetal thymus. We developed a methodology to track vector integration sites (VIS) in a mere 25µl of mouse blood for longitudinal and quantitative clonal analysis of human HSPC repopulation in mouse environment. We explored transcriptional and epigenetic features of human HSPC for possible VIS bias. Results 897 HSPC clones were longitudinally tracked in BLT mice—providing a first-ever demonstration of clonal dynamics and competitive expansion of therapeutic and control vector-modified human cell populations simultaneously repopulating in the same humanized mice. The polyclonal repopulation stabilized at 19 weeks post-transplant and the contribution of the largest clone doubled within 4 weeks. Moreover, 550 (∼60%) clones persisted over 6 weeks and were highly shared between different organs. The normal clonal profiles confirmed the safety of our gene therapy vectors. Multi-omics analysis of human FL-HSPC revealed that 54% of vector integrations in repopulating clones occurred within ±1kb of H3K36me3-enriched regions. Conclusions Human repopulation in mice is polyclonal and stabilizes more rapidly than that previously observed in humans. VIS preference for H3K36me3 has no apparent negative effects on HSPC repopulation. Our study provides a methodology to longitudinally track clonal repopulation in small animal models extensively used for stem cell and gene-therapy research and with lentiviral vectors designed for clinical applications. Results of this study provide a framework for understanding the clonal behavior of human HPSC repopulating in a mouse environment, critical for translating results from humanized mice models to the human settings.
Keywords: Repopulation; Humanized mouse; clone (Java method); Virus-based gene therapy research